Study of the Effect of Two Phases in Li4SiO4–Li2SiO3 Ceramics on the Strength and Thermophysical Parameters - Kozlovskiy, Artem; Shlimas, Dmitriy I.; Zdorovets, Maxim V.; Moskina, Aleksandra; Pankratov, Vladimir; Popov, Anatoli I. (MDPI, 2022)
The paper studies the effect of Li2SiO3/Li4SiO4 phase formation in lithium-containing ceramics on the strength and thermophysical characteristics of lithium-containing ceramics, which have great prospects for use as blanket materials for tritium propagation. During the phase composition analysis of the studied ceramics using the X-ray diffraction method, it was found that an increase in the lithium component during synthesis leads to the formation of an additional orthorhombic Li2SiO3 phase, and the main phase in ceramics is the monoclinic Li4SiO4 phase. An analysis of the morphological features of the synthesized ceramics showed that an increase in the Li2SiO3 impurity phase leads to ceramic densification and the formation of impurity grains near grain boundaries and joints. During determination of the strength characteristics of the studied ceramics, a positive effect of an increase in the Li2SiO3 impurity phase and dimensional factors on the strengthening and increase in the resistance to external influences during compression of ceramics was established. During tests for resistance to long-term thermal heating, it was found that for two-phase ceramics, the decrease in strength and thermophysical characteristics after 500 h of annealing was less than 5%, which indicates a high resistance and stability of these ceramics in comparison with single-phase orthosilicate ceramics. © 2022 by the authors. --//-- This is an open access article Kozlovskiy A., Shlimas D.I., Zdorovets M.V., Moskina A., Pankratov V., Popov A.I. "Study of the Effect of Two Phases in Li4SiO4–Li2SiO3 Ceramics on the Strength and Thermophysical Parameters" (2022) Nanomaterials, 12 (20), art. no. 3682, DOI: 10.3390/nano12203682 published under the CC BY 4.0 licence.
This research was funded by the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan (No. BR11765580). The research of the team from Latvia (A.M., V.P. and A.I.P.) has been carried out within the framework of the EUROfusion Consortium, funded by the European Union via the Euratom Research and Training Programme (Grant Agreement No. 101052200—EUROfusion). Views and opinions expressed are however those of the author(s) only and do not necessarily reflect those of the European Union or the European Commission. Neither the European Union nor the European Commission can be held responsible for them. The research was partly (A.M., V.P. and A.I.P.) performed in the Center of Excellence of the Institute of Solid State Physics, University of Latvia, supported through European Unions Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; blankets; hardness; lithium orthosilicate; lithium-containing ceramics; phase composition; strength